2021
DOI: 10.1186/s12941-021-00418-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between antimicrobial resistance and biofilm formation capability among Klebsiella pneumoniae strains isolated from hospitalized patients in Iran

Abstract: Background Klebsiella pneumoniae is a common cause of nosocomial infections. Antibiotic resistance and ability to form biofilm, as two key virulence factors of K. pneumoniae, are involved in the persistence of infections. The purpose of this study was to investigate the correlation between antimicrobial resistance and biofilm formation capability among K. pneumoniae strains isolated from hospitalized patients in Iran. Methods Over a 10-month period… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
6
25
2
Order By: Relevance
“…In our study, the most prevalent genes were entB (95.9%), mH (94.6%), mrkD (90.5%), and mrkA (75.7%). Consistently, previous studies have shown that mH, mrkD, mrkA and entB genes are among the most common virulence genes in K. pneumoniae strains (Sei et al 2016;Shadkam et al 2021). The rate of the entB was similar to the report of Mirzaie et al (Mirzaie and Ranjbar 2021).…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the most prevalent genes were entB (95.9%), mH (94.6%), mrkD (90.5%), and mrkA (75.7%). Consistently, previous studies have shown that mH, mrkD, mrkA and entB genes are among the most common virulence genes in K. pneumoniae strains (Sei et al 2016;Shadkam et al 2021). The rate of the entB was similar to the report of Mirzaie et al (Mirzaie and Ranjbar 2021).…”
Section: Discussionsupporting
confidence: 87%
“…However, there are many studies that showed isolation of Enterobacterales, non-fermenting P. aeruginosa and A. baumannii from clinical samples and established infection from rectal colonization. [34][35][36][37] Some studies from Mongolia also showed presence of extended-spectrum β-lactamase-producing E. coli, Klebsiella spp. and A. baumannii from clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, for P. aeruginosa and K. pneumonia , these values were higher ( P. aeruginosa MIC = 4 μM, MBC = 8 μM; K. pneumoniae MIC = 2 μM, MBC = 8 μM). A possible reason is that P. aeruginosa and K. pneumoniae tend to secrete extracellular polysaccharide matrix, which hinders the effect of peptides on bacteria ( 16 , 17 ). Studies have shown that capsular polysaccharides released by K. pneumoniae and alginate secreted by P. aeruginosa shield AMPs, causing conformational changes in them and preventing their interaction with microbial membranes ( 18 ).…”
Section: Discussionmentioning
confidence: 99%